The Secession Decorative Elements in the Residential Architecture in Belgrade in the Early 20th Century - Milosavljevic, Angelina; Stefanović, Tadija (Arhitektura i urbanizam, 2021)
The tendency towards modernization is noticeable in Belgrade’s architecture from the beginning of the 20th century, in the form of stylistic norms adopted from the Vienna Secession, which was the medium through which the forces of the reforms in architecture, culture and art were incorporated in the overall processes of modernization of in The Kingdom of Serbia. These processes reflect the cultural strivings of Serbian society, the efforts to demonstrate its cosmopolitan spirit, and the need to elevate and complement its historicist architectural stock, grounded in academic and national models, with more modern elements. In the architecture of the Serbian capital, the Secession brought together and conciliated, in a way, these two tendencies. Only a small number of buildings were composed in the dominant Secession style, with the basic characteristics of dissolution and negation of the earlier compositional schemes of strictly symmetrical horizontal and tripartite, or quinquepartite division of façades with risalits and enclosed façades, as well as conspicuous cornices and friezes, pilasters, framed portals and windows. The Secession’s decorative schemes were gradually introduced into the architecture of Belgrade as an authentic depository of a new decorative programme that consisted of both typical and original floral, anthropomorphic, zoomorphic and geometric ornaments, which replaced the classical repertory. This was especially prominent in the residential architecture that carried the ideas of the Secession. Therefore, one of the main goals of this essay is to interpret the role of the Secession in residential architecture in Belgrade from the beginning of the 20th  century, and to introduce some of its lesser-known examples.
Keywords: Belgrade; Secession; architecture; street façades; decoration